The identity of Celonites montanus Mocsáry, 1906 (Hymenoptera: Vespidae: Masarinae) and its first record from Kazakhstan - Fateryga, Alexander V.; Fadeev, Kirill I. (Zootaxa, 2023)
Celonites montanus Mocsáry, 1906, described from the Alai Range in Kyrgyzstan, is synonymized with C. kostylevi Panfilov, 1961, syn. nov. and C. haemorrhoidalis Gusenleitner, 2012, syn. nov. (both also described from Kyrgyzstan). The species is reported from Kazakhstan (Almaty Province) for the first time. It was collected at nototribic flowers of Lagochilus platyacanthus Rupr. (Lamiaceae). Trophic relationships between C. montanus and its forage plant are discussed.